Pendidikan Agama Islam dan Pembentukan Intelegensia Muslim Sebagai Kelas Sosial Baru: Tinjauan Sosiologi Pendidikan - Kalam Mahardika; Nurul Humaidi (Civiliza Publishing, Indonesia., 2026)
The development of Indonesian Muslim society in the modern era is marked by the emergence of Muslim intellectual groups that hold strategic positions in education, bureaucracy, economics, politics, and knowledge production. This phenomenon shows that Islamic Religious Education (PAI) not only serves to transmit religious values but also helps form new social groups with intellectual, cultural, and religious capital. This study aims to analyze the role of PAI in the process of forming Muslim intelligence as a new social class through the perspective of the sociology of education. The research uses a qualitative approach, specifically library research. Data were obtained from books, scientific journal articles, and academic documents relevant to the themes of Islamic education, Muslim intellectuals, and social stratification. Data analysis is carried out through content analysis techniques and critical interpretation of various literature sources. The results of the study show that PAI serves as an instrument of social mobility through internalizing values, mastering knowledge, forming an intellectual ethos, and accumulating cultural capital. This group not only serves as an agent for the reproduction of Islamic values but also as an actor in social transformation that bridges Islamic tradition and the demands of modernity. This research confirms that PAI has a strategic contribution in giving birth to a Muslim intelligence class that plays an important role in the development of contemporary Muslim society.